Dominant Heavy Metal Contaminants in Groundwater in the Vicinity of Municipal Solid Waste Sites: A Global Synthesis of Studies from 2015 to 2025 - Barem Talang Rasa; Intan Supraba; Fikri Faris (School of Postgraduate Studies, Diponegoro Univer, 2026)
Groundwater contamination by heavy metals originating from Municipal Solid Waste (MSW) landfill leachate poses a significant threat to human health and environmental sustainability. This issue is often exacerbated by inadequate leachate management systems, limited monitoring capacity, and the heterogeneous composition of solid waste entering landfills. This study aims to identify the most frequently detected and dominant heavy metals that pollute groundwater near MSW landfill sites. Employing a Systematic Literature Review (SLR) approach, ten primary research articles published between 2015 and 2025 were thoroughly analyzed. Article selection followed strict inclusion and exclusion criteria, including landfill location, number of metals analyzed, data accessibility, and relevance to the study context. The synthesized data evaluated study sites, sampling procedures, types of heavy metals tested, water quality standards applied, and regulatory exceedance status. The findings proves that chromium (Cr), lead (Pb), and cadmium (Cd) are the most frequently reported and most commonly exceeding safe limits. Iron (Fe) also shows a notable tendency to exceed standards, despite being analyzed less frequently. Zinc (Zn), on the other hand, appeared in all studies but rarely surpassed regulatory thresholds. These five metals—Cr, Pb, Cd, Fe, and Zn—are classified as priority contaminants in groundwater quality monitoring and risk-based remediation planning. This study contributes important scientific evidence for strengthening landfill leachate management strategies, improving regulatory frameworks, and enhancing long-term public health protection through focused groundwater monitoring initiatives.